Kompres Jahe Hangat dapat Menurunkan Intensitas Nyeri pada Pasien Gout Artritis - Radhika Radharani (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Arthritis gout is an inflammation process due to inflammation on cristal sour tendon in tissue around the joint.. Non pharmacology action for the patients of Arthritis Gout is warm ginger compress. The effects of heat from a warm ginger compress will cause vasodilation of blood vessels and increases blood flow to the body with pain resulting in a decrease in pain Objective : To know that warm ginger compress can decrease pain intensity in patients with arthritis gout Methods : Using literature studies from national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results : Warm ginger compresses can reduce pain of arthritis Gout. It is a traditional treatment or alternative therapy to reduce pain Gout Arthritis. It contains cyclo-oxygenation enzymes which can reduce inflammation in patients with Arthritis Gout, besides ginger also has a pharmacological effect of burning sensation and spicy, where this heat can relieve pain, stiffness and muscle spasm or the occurrence of vascular vasodilation, maximum benefits will be achieved within 20 minutes after heat application. Conclusion: Warm compresses of ginger can reduce arthritis gout pain. Ginger compress is a traditional treatment or alternative therapy to reduce gouty arthritis pain. Warm ginger compresses contain cyclo oxygenation enzymes which can reduce inflammation in gouty arthritis of sufferers.